Handbook of Reference Methods for Plant Analysis - Kalra, Yash P; Ed (CRC PRESS, 1998)
A resource of plant analysis procedures, outlined in easy-to-follow steps and laboratory-ready for implementation. It discusses plant laboratory preparation methods such as dry ashing and acid and microwave digestion. It is suitable for plant scientists in production agriculture, forestry, horticulture, and environmental sciences.